2012
DOI: 10.1259/bjr/91540172
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted imaging in uterine artery embolisation: do findings correlate with contrast enhancement and volume reduction?

Abstract: Objectives The objective of this study was to determine the role of diffusion-weighted imaging (DWI) in uterine artery embolisation (UAE), and to assess the apparent diffusion coefficient (ADC) of the dominant fibroid and its relationship to contrast enhancement and fibroid volume reduction. Methods We carried out a retrospective study of 15 patients who underwent UAE. Calculations were performed at baseline and 6 months post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Our fi ndings also suggest that ADC is an independent predictor of fi broid shrinkage. Fibroids with higher ADC values pre-UAE demonstrated greater shrinkage, which has been reported in other retrospective and prospective investigations (9,15,17). It is unclear what the degree of diff usion restriction of water molecules signifi es, but ADC provides some information about the molecular and/or cellular composition of masses including fi broids, and it may be useful in pre-UAE patient selection.…”
Section: Resultsmentioning
confidence: 56%
“…Our fi ndings also suggest that ADC is an independent predictor of fi broid shrinkage. Fibroids with higher ADC values pre-UAE demonstrated greater shrinkage, which has been reported in other retrospective and prospective investigations (9,15,17). It is unclear what the degree of diff usion restriction of water molecules signifi es, but ADC provides some information about the molecular and/or cellular composition of masses including fi broids, and it may be useful in pre-UAE patient selection.…”
Section: Resultsmentioning
confidence: 56%
“…Fibroids with higher ADC values pre-UAE demonstrated greater shrinkage, which has been reported in other retrospective and prospective investigations [9,15,17]. It is unclear what the degree of diffusion restriction of water molecules signifies, but ADC provides some information about the molecular and/or cellular composition of masses including fibroids, and it may be useful in pre-UAE patient selection.…”
Section: Discussionmentioning
confidence: 53%
“…Liapi et al evaluated 32 fibroids in 11 patients treated with UAE and found a significant drop in post-UAE ADC value across a follow-up interval of 99–239 days [ 9 ]. Ananthakrishnan et al also showed that post-UAE ADC measured from 15 patients was lower than pre-UAE ADC at 6-month follow-up [ 10 ]. Faye et al further studied the ADC changes in 27 fibroids in 17 patients at 1-week and 6-month follow-ups and reported a continued ADC decrease relative to pre-UAE measurement [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Faye et al further studied the ADC changes in 27 fibroids in 17 patients at 1-week and 6-month follow-ups and reported a continued ADC decrease relative to pre-UAE measurement [ 11 ]. Liapi et al and Ananthakrishnan et al proposed that the drop in ADC following UAE might depend on the acute microscopic changes like dehydration [ 9 , 10 ]. However, it should be emphasized that there may be progressive liquefaction of fibroids with increasing time between UAE and follow-up MRI [ 7 ].…”
Section: Discussionmentioning
confidence: 99%